Chronic low‐level JUUL aerosol exposure causes pulmonary immunologic, transcriptomic, and proteomic changes. Issue 2 (25th January 2023) - Been, Terek; Alakhtar, Bayan; Traboulsi, Hussein; Tsering, Thupten; Bartolomucci, Alexandra; Heimbach, Nicole; Paoli, Sofia; Burnier, Julia; Mann, Koren K.; Eidelman, David H.; Baglole, Carolyn J.
Abstract: E‐cigarettes currently divide public opinion, with some considering them a useful tool for smoking cessation and while others are concerned with potentially adverse health consequences. However, it may take decades to fully understand the effects of e‐cigarette use in humans given their relative newness on the market. This highlights the need for comprehensive preclinical studies investigating the effects of e‐cigarette exposure on health outcomes. Here, we investigated the impact of chronic, low‐level JUUL aerosol exposure on multiple lung outcomes. JUUL is a brand of e‐cigarettes popular with youth and young adults. To replicate human exposures, 8‐ to 12‐week‐old male and female C57BL/6J mice were exposed to commercially available JUUL products (containing 59 mg/ml nicotine). Mice were exposed to room air, PG/VG, or JUUL daily for 4 weeks. After the exposure period, inflammatory markers were assessed via qRT‐PCR, multiplex cytokine assays, and differential cell count. Proteomic and transcriptomic analyses were also performed on samples isolated from the lavage of the lungs; this included unbiased analysis of proteins contained within extracellular vesicles (EVs). Mice exposed to JUUL aerosols for 4 weeks had significantly increased neutrophil and lymphocyte populations in the BAL and some changes in cytokine mRNA expression. However, BAL cytokines did not change. Proteomic and transcriptomic analysis revealed significant changes in numerous biological pathways including neutrophil degranulation, PPAR signaling, and xenobiotic metabolism. Thus, e‐cigarettes are not inert and can cause significant cellular and molecular changes in the lungs.